Economic benefits of improved accessibility to transport systems and the role of transport in fostering tourism for all - Markus Rebstock (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
Accessibility is one of the key aspects of current transport planning, especially in reliance to public transport and pedestrian traffic facilities. This paper deals with this subject by outlining which are or could be the benefits of improved accessibility to the transport system with a special focus on economic benefits and the tourism sector. Therefore selected existing studies will be analysed. Besides the legal background and social aspects of accessibility related to the transport sector will be covered. The first section deals with the legal background and social aspects of accessibility in the transport sector. It shows that nowadays in many countries accessibility of transport systems is not a voluntary task but a task bound by law and that an accessible environment is not only essential for people with disabilities and necessary for up to 40 % of the population but also a matter of comfort for all users. The second section outlines which are or could be the economic benefits of improved accessibility to the transport system. Two studies from Norway used the stated preference method to monetise and prioritise different universal design measures. In general this method seems to work also as a tool for analysing economic benefits of accessibility measures. Nevertheless the results of these studies have to be interpreted with extremely caution in order to avoid discrimination. The third section deals with the economic impact of accessible tourism using the example of Europe. The inducible impact of accessible tourism on the transport sector as well as the relevance of passenger transportation for accessible tourism is elaborated. All in all accessible tourism produces a huge economic impact on the tourism sector and beyond, and by improving accessibility in the future a significant raise of economic benefits is possible. In general traffic is precondition for tourism. Besides tourists spend a significant part of their travel expenses for the journey to the destination and back and for local transportation. This makes it clear that accessible transport systems will directly benefit from an increasing accessible tourism market.
Keywords: 330; Verkehrsinfrastruktur; Räumliche Erreichbarkeit; Behindertenpolitik; Behinderte; Ältere Menschen; Tourismus; Partizipation; EU-Staaten